The Benefits of Pollen to Honey Bees: ENY152/IN868, 9/2010 - Ellis, Amanda; Ellis, James D.; O'Malley, Michael; Zettel Nalen, Catherine M. (EDIS, 2010)
ENY152, a 4-page illustrated fact sheet by Amanda Ellis, Jamie Ellis, Michael O’Malley, and Catherine Zettel Nalen, provides an overview of the nutritional needs of honey bees with an emphasis on the role of pollen — nutritional content, where it is produced, how it is collected, and how to ensure colony nutrition. Published by the UF Department of Entomology and Nematology, September 2010. ENY152/IN868: The Benefits of Pollen to Honey Bees (ufl.edu)